Rapid Scan EPR imaging as a Tool for Magnetic Field Mapping - Tseytlin, Oxana (Appl Magn Reson, 2020)
Functional four-dimensional spectral-spatial electron paramagnetic imaging (EPRI) is routinely used in biomedical research. Positions and widths of EPR lines in the spectral dimension report oxygen partial pressure, pH, and other important parameters of the tissue microenvironment. Images are measured in the homogeneous external magnetic field. An application of EPRI is proposed in which the field is perturbed by a magnetized object. A proof-of-concept imaging experiment was conducted, which permitted visualization of the magnetic field created by this object. A single-line lithium octa-n-butoxynaphthalocyanine spin probe was used in the experiment. The spectral position of the EPR line directly measured the strength of the perturbation field with spatial resolution. A three-dimensional magnetic field map was reconstructed as a result. Several applications of this technology can be anticipated. First is EPRI/MPI co-registration, where MPI is an emerging magnetic particle imaging technique. Second, EPRI can be an alternative to magnetic field cameras that are used for the development of high-end permanent magnets and their assemblies, consumer electronics, and industrial sensors. Besides the high resolution of magnetic field readings, EPR probes can be placed in the internal areas of various assemblies that are not accessible by the standard sensors. Third, EPRI can be used to develop systems for magnetic manipulation of cell cultures.